The impact of COVID-19 and locust invasion on farm households in Punjab and Sindh analysis from cross sectional surveys in Pakistan - Yamano, Takashi; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This paper presents results of a survey on the impacts of the COVID19 pandemic and a simultaneous locust invasion on farmers harvests, marketing efforts, input prices, and financial needs in two provinces in Pakistan.
Keywords: Agriculture -- Economic aspects; Economic development; Natural resource -- Pakistan; Electronic book